Practical assessment of nanoscale indentation techniques for the biomechanical properties of biological materials. (July 2016) - Chang, Alice Chinghsuan; Liao, Juinn-Der; Liu, Bernard Haochih
Highlights: The measured elastic modulus is affected by both the probe geometry and sample condition. The proper selection of the contact mechanism model can increase the accuracy of modulus estimation. The suitable applications of nanoindentation on various biological materials are summarized. Abstract: Nanoindentation on biological materials reveals the surface response to an external load. The load– or force–displacement information, as obtained by Z -axis sensitive nanoindenter or an atomic force microscope, is usually converted into general relations of elastic modulus and hardness, which are thereafter associated with the indented surface properties of biological materials. In spite of the growing popularity of nanoindentation in the field of biological research, the measured deviations caused by the factors, such as the experimental variables and the intrinsic surface characteristics of samples, have not been well studied. This review thus examines the issue of nano-mechanical measurements, and particularly how these are influenced by the probe geometry, penetration depth, and contact mechanism model used, as well as the appropriate use of the related instruments. We propose a guideline for experimental settings of various biological specimens, and provide suggestions for future area of applications. Graphical abstract: